Juridical Review of Delivery Practices outside the Indonesian Health Service Facilities - Saputera, Yandi; Razy, Fakhruddin; Sinta, Selly Hestiani (International Journal of Law and Public Policy (IJLAPP), 2023)
Childbirth is a process that is awaited by all pregnant women who are expected to run smoothly because the delivery process does not always run without obstacles, especially if it is not carried out by health workers and with adequate medical equipment. A delivery may be considered quite dangerous for pregnant women if in practice there are no tools and places that meet labor standards to support the delivery process for pregnant women. This study was made to find out how the legal system in Indonesia regulates the practice of childbirth carried out outside the available health service facilities such as health centers, hospitals, and midwife independent practice facilities. The method in this study is normative legal research, namely by researching library materials by analyzing the arrangements in various statutory provisions and through data contained in several literatures. Based on the discussion and research results that the practice of childbirth carried out outside the health care facility is allowed by taking into account the statutory regulations and policies of the local government.